2015
DOI: 10.1111/lasr.12125
|View full text |Cite
|
Sign up to set email alerts
|

The Legalization of Emotion: Managing Risk by Managing Feelings in Contracts for Surrogate Labor

Abstract: Despite a rich literature in law and society embracing contracts as exchange relations, empirical work has yet to consider their emotional dimensions. I explore the previously unmapped case of surrogacy to address the interface of law and emotions in contracting. Using 115 semistructured interviews and content analyses of 30 surrogacy contracts, I explain why and how lawyers, with the help of matching agencies and counselors, tactically manage a variety of emotions in surrogates and intended parents before, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Many studies (some with overlapping samples) focus solely or mainly on surrogacy practices in a single country, e.g. thirteen on Indian (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), nine on the US (32)(33)(34)(35)(36)(37)(38)(39)(40), and five articles on the Israeli context (36,(41)(42)(43)(44). The least studied country contexts in this sample include Greece 45, Iran (46), Italy (47), Mexico (48,49), Norway (50), Sweden (51,52), and Russia/Ukraine (53,54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies (some with overlapping samples) focus solely or mainly on surrogacy practices in a single country, e.g. thirteen on Indian (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), nine on the US (32)(33)(34)(35)(36)(37)(38)(39)(40), and five articles on the Israeli context (36,(41)(42)(43)(44). The least studied country contexts in this sample include Greece 45, Iran (46), Italy (47), Mexico (48,49), Norway (50), Sweden (51,52), and Russia/Ukraine (53,54).…”
Section: Resultsmentioning
confidence: 99%
“…Contact before and after the birth is regulated by the contract, including: (1) lifestyle rules and behavioural restrictions; (2) rules governing breastfeeding, and 'intimate' form of contact with the baby; and (3) rules governing viewing, handling, and future relationships with the newborn (37). The expectations of both parties are often fulfilled to a large extent, based on contractual regulations: I'm satisfied, it's what we wanted.…”
Section: Structured Relationshipsmentioning
confidence: 99%
“…Surrogacy not only challenges the traditional alignment of mother-child bonds but also "nurtures parents-to-be" through interpretive and relational work (Berend 2016; Teman 2010). A variety of professionals in the reproductive field-from lawyers, to matching agencies, to psychologists-use contract provisions, practices, and emotion management techniques to manage risk and constitute identity, simultaneously legalizing and reconstructing gender and family paradigms (Berk 2015).…”
Section: Law Society and Gender In Exchange Relationsmentioning
confidence: 99%
“…More research is needed especially on the roles played by counseling and consenting mechanisms. Beck's work on contracting of emotion may serve as a useful starting point as her examination of surrogacy arrangements documents the loss of autonomy expected of surrogates [113].…”
Section: Surrogate Arrangements Are Complicated: Making Informed Decimentioning
confidence: 99%
“…Applicability to surrogate IVF treatment, prenatal care, delivery, and infant medical coverage remains uncertain [90,118]. Where state law permits surrogacy or is silent about it, medical expenses and insurance coverage often form elements of surrogacy arrangements and contracts and may be embedded in law [90,113]. For example, the Fuchs and Berenson study reported that 94% of surveyed gestational surrogates had private medical insurance [112].…”
Section: Mandated Embryo Transfer Limits and Insurance Coveragementioning
confidence: 99%